Homo Sacer sebagai Figur Politis dan Kaitannya dengan Dunia Pendidikan Tinggi - Ferdinand Indrajaya (Bina Nusantara University, 2011)
Article is an outcome from writer’s reflection from his reading on Homo Sacer, Sovereign Power and Bare Life, a book by Giorgio Agamben, an Italian 20th century philosopher. The reading concerns with the three chapters which are Homo Sacer, The Ambivalence of The Sacred, and The Sacred Life, and also the preface of chapters. Generally, this article proposes two main things. First, Agamben’s description on Western modern political practice, developed from the Greek until today. Second, writer’s reflection on educational system in Indonesia, especially the higher education level in nowadays, through Agamben’s perspective. Structurally, article is divided into three parts. First, the Preface, is a general view to Agamben’s political thought which will stand as a background to the second part from this article, Homo Sacer. On the third part, Education as Bare Life, is writer’s reflection on higher education system in Indonesia borrowing the political perspectives from Agamben.